Retardation model in fatigue crack growth prediction of cylindrical pressure vessels and pipes subjected to variable amplitude of pressure cycling - Mohd Alfian bin Al-Junit (2023)
This project is predominantly software development based project concentrating on retardation models is fatigue crack growth prediction of cylindrical pressure vessels and pipes subjected to variable amplitude of pressure cycling. Cracks may occur due to several factors. It may occur due to stress and strain factor or geometry factor.